Navigating the digital transformation: industry 4.0's role in modern healthcare - Thongwichian, Phonchai (Frontiers on Healthcare Research, 2024)
Background: The advent of Industry 4.0 has ushered in a new era of technological advancements, significantly impacting various sectors, including healthcare. The integration of Industry 4.0 technologies such as artificial intelligence, the Internet of Things, and big data analytics promises to revolutionize healthcare systems, enhancing efficiency, accuracy, and patient outcomes. However, the rapid evolution of these technologies and their implications in healthcare necessitate a comprehensive understanding of current research trends, challenges, and future directions. Objective: This systematic literature review aims to analyze and synthesize the current body of research on the integration of Industry 4.0 technologies in healthcare. The review focuses on identifying key technologies, evaluating their impact on healthcare delivery, operational efficiencies, and policy implications, while highlighting challenges and potential areas for future research. Results: Analysis of articles from 2022 and 2023 revealed a significant focus on practical implementations of Industry 4.0 technologies in healthcare. Key findings include the prevalent use of data analytics and AI in enhancing patient care and operational efficiencies, and the emerging challenges related to data privacy and ethical considerations. The review also identified a shift from theoretical exploration to real-world applications of these technologies in healthcare settings. Conclusion: This study enriches the field of healthcare research by providing a contemporary overview of the integration of Industry 4.0 technologies in healthcare. It highlights the transition towards practical applications, underlines the critical challenges faced, and suggests future research directions. By synthesizing recent literature, this review offers valuable insights for healthcare professionals, policymakers, and technologists, guiding informed decision-making and fostering an interdisciplinary approach to successfully integrate Industry 4.0 technologies in healthcare.